Analysing the Legal Dynamics Involved in the Development of New Renewable Energy in Indonesia, Focussing on Regulations and the Challenges Faced During Implementation - Hendra Dinatha; Fauzie Yusuf Hasibuan; Basuki Rekso Wibowo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Energy is an essential requirement for civilisation, and due to the rapid expansion of the population in Indonesia, energy consumption has also experienced a substantial rise. Hence, it is crucial to utilise and enhance the capacity of sustainable energy resources present across the archipelago, including geothermal, hydropower, wind, bioenergy (including bioethanol, biodiesel, and biomass), ocean current energy, nuclear, and solar energy. Indonesia's energy strategy is currently focused on the use of renewable energy to decrease carbon emissions. This is backed by legislation that promotes the development of renewable energy programs under the National Energy strategy. This article evaluates the regulatory factors associated with the advancement of new renewable energy and its influence on the establishment of sustainable energy infrastructure in Indonesia. This research provides a comprehensive legal analysis of the changing regulations surrounding renewable energy. It examines how these regulations affect the establishment of sustainable energy infrastructure and investigates the current legal consequences. The study aims to understand how the regulatory framework can either support or impede the progress of renewable energy development. This research offers valuable insights on the role of legislation in facilitating the shift towards sustainable energy sources in Indonesia. It also sheds light on the potential obstacles and advantages that may arise during this transition.